CD44 mediates the catch-bond activated rolling of HEPG2Iso epithelial cancer cells on hyaluronan - Hanke, Maximilian; Sleeman, Jonathan P. (Cell adhesion & migration, 2017)
The attachment of cancer cells to the endothelium is an essential step during metastatic dissemination. The cell surface receptor CD44 is capable of binding to hyaluronan (HA) produced by tumor cells and by cells of the tumor microenvironment, including blood endothelial cells. Here, we investigated the role of CD44 in the interaction between the liver cancer cell line HepG2Iso and HA surfaces. The rolling interaction was quantitatively analyzed using a microfluidic shear force setup. It was found that rolling of the liver cancer cells on HA depends on CD44, which mediates a catch-bond interaction and thus a flow-induced rolling of the cells. Reduction of CD44 expression by means of siRNA, inhibition of the interaction of CD44 with HA by antibody blocking, and treatment with low molecular weight HA inhibited liver cancer cell rolling on HA-coated surfaces. The results not only clearly show the dependency of the shear-induced catch-bond interaction of HepG2Iso cells on CD44 and HA, but also for the first time demonstrate CD44-mediated rolling for epithelium-derived cells that are typically adherent.
Gesehen am 05.04.2018